Role-playing games of Japan: transcultural dynamics and orderings - Kamm, Björn-Ole (Palgrave Macmillan, 2020)
“At length, proponents of Japanese geek or otaku culture have been shunning both themselves and others asking about the relationship between games and reality. With the advent of this book, which should be titled “The otaku, or There and Back Again,” I believe that research on otaku finally gained a map to return from virtual reality to reality.” -- Ōtsuka Eiji, International Research Center for Japanese Studies, Japan “Kamm's book is an important look at an understudied culture of play, and a very fascinating, engaging read.” -- J. Tuomas Harviainen. Editor, Simulation & Gaming “A thoughtful analysis of Japanese role-playing habits which carefully analyses some of the key tropes and representations of the Japanese gamer. The author presents a well observed picture of the ways in which role-playing is understood, played and represented through Japanese culture and play practices. Overall, this provides a detailed study of how role-playing has developed and is understood as a cultural tool, and how this can be used to understand play practices around the world.” -- Esther MacCallum-Stewart, University of Sussex, UK This book engages non-digital role-playing games—such as table-top RPGs and live-action role-plays—in and from Japan, to sketch their possibilities and fluidities in a global context. Currently, non-digital RPGs are experiencing a second boom worldwide and are increasingly gaining scholarly attention for their inter-media relations. This study concentrates on Japan, but does not emphasise unique Japanese characteristics, as the practice of embodying an RPG character is always contingently realised. The purpose is to trace the transcultural entanglements of RPG practices by mapping four arenas of conflict: the tension between reality and fiction; stereotypes of escapism; mediation across national borders; and the role of scholars in the making of role-playing game practices. Björn-Ole Kamm teaches and researches in Transcultural Studies at Kyoto University. His previous research engaged stereotypes and media use in Japanese society. Currently, he explores live-action role-play in Japanese educational contexts.